Toponimi Nama-Nama Desa di Kabupaten Ponorogo (Kajian Antropolinguistik) - Prima Pandu Pertiwi; Suyanto Suyanto; Sri Puji Astuti (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
This study aims to categorize the toponymy based on its manifestation aspects, explain the meaning of village names, and identify the cultural values contained in the naming of villages in Ponorogo Regency. This research uses anthropolinguistic theory, toponymy, meaning, and cultural values. This research uses in-depth interview techniques and literature study to collect the data. The analysis method used is the descriptive ethnographic method. The results showed that 83 village names in Ponorogo Regency contained toponymy aspects based on the naming. The village toponymy category in Ponorogo Regency includes three naming aspects. The manifestation aspect is contained in 34 village names, social aspects in 39 village names, and cultural aspects in 11 village names. In terms of meaning, 32 village names contain advice, rules, patterns of thought related to Javanese customs culture in the local community. Besides, it also contains the cultural values of peace and prosperity.